Proceedings of the EACL 2014 Workshop on Humans and Computer-Assisted Translation 2014
DOI: 10.3115/v1/w14-0315
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Enabled Computer-Aided Translation: A Satisfaction Survey with Post-Editor Trainees

Abstract: The present study has surveyed post-editor trainees' views and attitudes before and after the introduction of speech technology as a front end to a computer-aided translation workbench. The aim of the survey was (i) to identify attitudes and perceptions among post-editor trainees before performing a post-editing task using automatic speech recognition (ASR); and (ii) to assess the degree to which post-editors' attitudes and expectations to the use of speech technology changed after actually using it. The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…This being said, over the past two decades, certain researchers, trainers and professionals have demonstrated an interest in using VR technology in translation [1,4,6,7,8,10,11,18,19,24,25]. However, none of today's off-the-shelf stand-alone VR systems was developed specifically for translation purposes.…”
Section: Background and Motivationsmentioning
confidence: 97%
See 1 more Smart Citation
“…This being said, over the past two decades, certain researchers, trainers and professionals have demonstrated an interest in using VR technology in translation [1,4,6,7,8,10,11,18,19,24,25]. However, none of today's off-the-shelf stand-alone VR systems was developed specifically for translation purposes.…”
Section: Background and Motivationsmentioning
confidence: 97%
“…One possible way to do this is by enabling multimodal interaction. In a recent study by MesaLao [19], student translators surveyed reported that they would welcome the integration of voice input as one of the possible input modes for performing translation tasks. Indeed, 80% of respondents stated that they would definitely consider adopting VR in combination with non-speech input modes in their daily work as translators.…”
Section: Background and Motivationsmentioning
confidence: 98%
“…A more recent approach, called SEECAT (Martinez et al, 2014), investigates the use of automatic speech recognition (ASR) in PE and argues that its combination with typing could boost productivity. A survey regarding speech usage with PE trainees (Mesa-Lao, 2014) finds that they have a positive attitude towards speech input and would consider adopting it, but only as a complement to other modalities. In a small-scale study, Zapata et al (2017) found that ASR for PE was faster than ASR for translation from scratch.…”
Section: Multi-modal Approachesmentioning
confidence: 99%
“…While most computer-aided translation (CAT) tools focus on traditional translation and incorporate only mouse & keyboard, previous research investigated other input modalities: automatic speech recognition (ASR) for dictating translations has already been explored in the 90s (Dymetman et al, 1994;Brousseau et al, 1995) and the more recent investigation of ASR for PE (Martinez et al, 2014) even argues that a combination with typing could boost productivity. Mesa-Lao (2014) finds that PE trainees have a positive attitude towards speech input and would consider adopting it, and Zapata et al (2017) found that ASR for PE was faster than ASR for translation from scratch. Due to these benefits, commercial CAT tools like memoQ and MateCat are also beginning to integrate ASR.…”
Section: Introduction and Related Workmentioning
confidence: 99%